Perancangan User Interface Sistem Informasi OSIS berbasis Android dengan pendekatan Human Centered Design Studi Kasus SMKN 1 Dlanggu - Desi Fatmawati; Hanifah Muslimah Az-Zahra; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
OSIS is the main organization for schools that aims to mobilize students in channeling talents and creative ideas. The OSIS organization at SMKN 1 Dlanggu plays an important role for schools, especially information and activities carried out by the OSIS. Submission of information or OSIS activities such as the election of the OSIS chairman and information on OSIS events is still done manually, meaning that there is no well-integrated system. This activity carried out is still not efficient. Based on these problems, the researcher designed the OSIS information system user interface to help select the OSIS chairman, convey information on activities efficiently and effectively. The design of the OSIS information system interface is to determine the needs of the user's system design display so that users can adjust the use of the system according to their needs. The results of the research are in the form of low fidelity wireframe designs and high fidelity prototypes which are evaluated by stakeholders as domain experts, namely OSIS supervisors and usability testing using user groups, namely one admin, three teachers and three students. System design testing is carried out iteratively and testing for the final results is carried out using usability testing with SUS assessment. The results of the test get a score with an average of 84.6 the results of this value indicate that the system design can be accepted by potential users.